Characterization of Historical Seasonal and Annual Rainfall and Temperature Trends in Selected Climatological Homogenous Rainfall Zones of Uganda - Majaliwa, J.G.M.; Tenywa, M.M.; Bamanya, D.; Majugu, W.; Isabirye, P.; Nandozi, C.; Nampijja, J.; Musinguzi, P.; Nimusiima, A.; Luswata, K.C.; Rao, K.P.C.; Bonabana-Wabbi, Jackline; et al. (Global Journals Inc. (USA), 2015)
There is general lack of scientific consensus on the trend and distribution of annual and seasonal rainfall and temperature in Uganda. This study used both observational and AgMerra rainfall and temperature data for the period 1980-2010 to characterize the trend and variability in seasonal and annual rainfall, maximum and minimum temperatures across 12 different rainfall homogenous zones (K, H, ME, L, J, F, MW, D, E, A1, A2, and I) of Uganda. Trends analysis was done using regression method, while coefficient of variation and ANOVA techniques were used to analyze variability. The results show statistically significant increasing trends (P ? 0.05) in annual rainfall amount in zone A1 and a declining trend for zone K (P<0.05).